The AVR2–SIX5 gene pair is required to activate I‐2‐mediated immunity in tomato. Issue 2 (13th May 2015) - Ma, Lisong; Houterman, Petra M.; Gawehns, Fleur; Cao, Lingxue; Sillo, Fabiano; Richter, Hanna; Clavijo‐Ortiz, Myriam J.; Schmidt, Sarah M.; Boeren, Sjef; Vervoort, Jacques; Cornelissen, Ben J. C.; Rep, Martijn; et al.
Summary Plant‐invading microbes betray their presence to a plant by exposure of antigenic molecules such as small, secreted proteins called 'effectors'. In Fusarium oxysporum f. sp. lycopersici (Fol) we identified a pair of effector gene candidates, AVR2‐SIX5, whose expression is controlled by a shared promoter. The pathogenicity of AVR2 and SIX5 Fol knockouts was assessed on susceptible and resistant tomato (Solanum lycopersicum) plants carrying I‐2. The I‐2 NB‐LRR protein confers resistance to Fol races carrying AVR2. Like Avr2, Six5 was found to be required for full virulence on susceptible plants. Unexpectedly, each knockout could breach I‐2‐mediated disease resistance. So whereas Avr2 is sufficient to induce I‐2‐mediated cell death, Avr2 and Six5 are both required for resistance. Avr2 and Six5 interact in yeast two‐hybrid assays as well as in planta. Six5 and Avr2 accumulate in xylem sap of plants infected with the reciprocal knockouts, showing that lack of I‐2 activation is not due to a lack of Avr2 accumulation in the SIX5 mutant. The effector repertoire of a pathogen determines its host specificity and its ability to manipulate plant immunity. Our findings challenge an oversimplified interpretation of the gene‐for‐gene model by showing requirement of two fungal genes for immunity conferred by one resistance gene.